ROLE OF STATE AND COMMUNITY IN PRESERVATION OF SHAIVA TRADITIONS (WITH SPECIAL REFERENCE TO BILASPUR DISTRICT) - Anju Tiwari; Dubey, Mahendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Shaiva traditions have been an integral part of Indian culture and religion, whose deep Shaiva roots have spread in this land for thousands of years. Both the state and the community have played an important role in preserving these traditions. While the state has been actively involved in preserving and promoting religious traditions through its policies and programmes, the community has fulfilled its social and religious responsibilities to keep these traditions alive. At the state level, the maintenance of religious places, preservation of Shaivite temples, promotion of Shaivite literature and scriptures, and promotion of the importance of Shaivite cultures have been important aspects. These traditions pervade various social aspects of the family and society, such as worship, festival celebrations and expressions of faith. The followers of the Shaivite sect perform their religious duties by following these traditions in their daily lives. This not only preserves traditions, but also builds religious tolerance and unity in the society. The aim of this research is to understand how both the state and the community preserve and promote Shaivite traditions.